The sport career of Brazilian paralympic athlete: the legacies of Paralympic mega events and the financial support to the Paralympians - Haiachi, M.; Mataruna, L.; Guimaraes-Mataruna, A.; Cardoso, G. (8th International Sport Business Symposium, 2016)
This research forms part of the EU sponsored Carnival IRSES project coordinated by Coventry University, UK. The focus of this research is the sporting career of the Brazilian Paralympic athlete. The hosting of the Rio 2016 Paralympic Games represents a new opportunity for Brazilian Paralympic athletes. In addition it is claimed that this increased visibility of Paralympic sport can change societal perceptions regarding disability and increase investment in high performance sport for athletes with disabilities. Successful results obtained in international Paralympic sporting events have also assisted Brazilian athletes to gain increased financial support and improved training conditions. The success of Brazilian Paralympians in these events has also inspired a new generation of disabled people to become Paralympic athletes as a career option. However, this is a career that is still full of uncertainty due the investment in Paralympic sport being so dependent upon results and the economic situation within the country. Although many athletes are investing, their time in trying to consolidate sport as a career their success in doing so is not dependent only upon their results but also in their ability to maintain high performance levels over a long period. The study aims to critically analyse the career of Brazilian Paralympic athlete. The methodology applied was a document analysis of the Brazilian Paralympic Committee (BPC) and the Ministry of Sport from 2009 to 2016. Institutional documents, official websites and reports were analysed. The results showed that the Brazilian Paralympic athlete career is divided into four different categories: 1) Medal success; 2) financial resources; 3) training conditions; 4) the management of the athlete`s image. With regard to medal success the starting point for the research was the Toronto Paralympic Games (1976) when the first Brazilian Paralympic medal was achieved. Since then the country has won 229 medals (73 gold, 83 silver and 73 bronze). However, despite the fact that 803 athletes have represented the Brazilian team at a Paralympic Games between 1972 to 2012 only 127 athletes (80% male and 20% female) have actually won medals. In respect of the financial resources a new law in 2015 dictated that 2.7% of all national lottery income be allocated to the Brazilian Olympic and Paralympic Committees, with 37.04% of this total destined for the Paralympic Committee. In addition, the Ministry of Sport contributed to the development of Paralympic sport in 2004 with the introduction of the `Bolsa Atleta` programme that incentivized athletes to dedicate more hours in training by the introduction of financial rewards. The third analysis investigated the barriers that affect the training and performance of Brazilian Paralympians including access to training facilities, equipment and the different kinds of support available (e.g. emotional, physical, staff and others). Finally, we investigated the management of the athlete image, the role of the media, particularly drawing sponsorship to the area and the role of the athletes in representing the Paralympic values of courage, determination, inspiration and equality. The BPC has been investing in the image in of their Paralympians since 2004. Since then they have faced the challenge of how to use the images of well-known Brazilian Paralympians in order to transform non-disabled perceptions of peoples with disabilities. Overall, the research highlights the increase in investment in training facilities in order to stimulate debate about the Paralympic movement within Brazil and to emphasise the use of sport as a tool for development and transformation.